Medications for Hypertension Change the Secretome Profile from Marrow Stromal Cells and Peripheral Blood Monocytes. (1st August 2020) - Satani, Nikunj; Giridhar, Kaavya; Cai, Chunyan; Wewior, Natalia; Norris, Dominique D.; Aronowski, Jaroslaw; Savitz, Sean I.
Abstract : Marrow stromal cells (MSCs) are in different stages of clinical trials for stroke patients. MSCs are proposed to promote recovery through the release of secretomes that modulate the function of beneficial immune cells. The majority of stroke patients have comorbidities including hypertension, for which they are prescribed antihypertensive medications that might affect the function of MSCs, when they are administered in stroke patients. Here, we studied the effects of common antihypertensive medications on the secretomes of human MSCs and their modulation of human monocytes (Mo) derived from stroke patients. MTT assay was used to assess the proliferation of MSCs after they were exposed to increased levels of antihypertensive medications. MSCs were exposed to the following medications: atenolol, captopril, and losartan. Monocytes were isolated from stroke patients with NIHSS ranging from 11 to 20 and from healthy controls. MSC-Mo cocultures were established, and a secretome profile was analyzed using the Magpix Multiplex cytokine array from Luminex technology. The linear mixed-effect model was used for statistical analysis. All analyses were performed using SAS 9.4, and p values less than 0.05 were considered significant. At clinically relevant levels, there was no change in MSC proliferation after exposure to atenolol, captopril, or losartan. Atenolol increased IL-1RA in stroke-Mo and decreased IL-8 secretion from MSCs indicating an anti-inflammatory effect of atenolol on secretomes of these cells. Captopril increased IL-8 from stroke-Mo and increased IL-6, IL-8, and MCP-1 secretions from MSCs. Captopril also increased IL-6 secretion from cocultures of stroke-Mo and MSCs indicating a strong proinflammatory effect on MSCs and their interaction with Mo. Atenolol increased the secretion of IL-8 and MCP-1 while captopril increased the secretion of IL-6 and MCP-1 from MSCs. Losartan decreased the release of IL-6 from MSCs. Losartan reduced MCP-1 and TNF- α from stroke-Mo and reduced IL-8 from cocultures of stroke-Mo and MSCs. Our results show that antihypertensive medications such as atenolol, captopril, and losartan, at concentrations comparable to doses prescribed for patients hospitalized for acute stroke, modulate the secretome profile of MSCs and their modulatory effects on target immune cells. Our results suggest that stroke trials involving the use of intravenous MSCs should consider the effect of these antihypertensive drugs administered to stroke patients.